(untitled) (Journal of Natural Language and Linguistics, 2025)
This study explores codeswitching and semiotic modes in 2023 Nigerian Presidential Campaign Advertisements. Three (3) political campaign advertisements and party logos from the three major Nigerian political parties, APC, PDP, and LP, alongside 200 survey responses, were analyzed using a mixed descriptive quantitative and qualitative data analysis method. The markedness theory and social semiotic theory were adopted in this study. Findings indicate that linguistic codeswitching and visual strategies such as salience, gaze, and foregrounding were used to perform certain rhetorical functions, such as wooing the electorate’s support and solidarity, ethnic and religious affiliations, party identity projection, and portraying the candidate’s positive identity by emphasizing the leadership skills that make them fit for the role. Despite the persuasive effects of the strategies, the survey responses indicated that voters also considered the previous performance of past leaders. Thus, while culturally informed language and visual strategies can enhance the appeal of a message, political campaign designers should also prioritize communicating performance-based credibility in their campaign resources.